Autonomous Reconstitution of Fractured Hybrid Perovskite Single Crystals. Issue 19 (29th March 2022) - Al‐Handawi, Marieh B.; Dushaq, Ghada; Commins, Patrick; Karothu, Durga Prasad; Rasras, Mahmoud; Catalano, Luca; Naumov, Panče
Abstract: The outstanding performance and facile processability turn hybrid organic–inorganic perovskites into one of the most sought‐after classes of semiconducting materials for optoelectronics. Yet, their translation into real‐world applications necessitates that challenges with their chemical stability and poor mechanical robustness are first addressed. Here, centimeter‐size single crystals of methylammoniumlead(II) iodide (MAPbI3 ) are reported to be capable of autonomous self‐healing under minimal compression at ambient temperature. When crystals are halved and the fragments are brought in contact, they can readily self‐repair as a result of a liquid‐like behavior of their lattice at the contact surface, which leads to a remarkable healing with an efficiency of up to 82%. The successful reconstitution of the broken single crystals is reflected in recuperation of their optoelectronic properties. Testing of the healed crystals as photodetectors shows an impressive 74% recovery of the generated photocurrent relative to pristine crystals. This self‐healing capability of MAPbI3 single crystals is an efficient strategy to overcome the poor mechanical properties and low wear resistance of these materials, and paves the way for durable and stable optoelectronic devices based on single crystals of hybrid perovskites. Abstract : Hybrid organic–inorganic perovskites (HOIPs) are a widely researched class of materials with prospects for a vast array of optoelectronic applications. In this work, it is demonstrated that broken centimeter‐sized crystals of a typical HOIP, MAPbI3, can self‐heal and are capable of mechanical and electrical recovery after mild compression of their fragments.